Interaction of the trade union organization with internal stakeholders of educational institution - Kozyaruk , S. (New Collegium, 2021)
This article analyzes the interaction of the trade union organization with the internal stakeholders of the educational institution on the example of the experience of the People’s Ukrainian Academy. The internal stakeholders of the educational and scientific complex have been identified: the staff (teachers, teaching and support staff), students, graduates, public organizations and councils of the academy; structural subdivisions, medical service, labor protection service; departments, sports club, etc. The main directions of the work of the trade union organization are allocated: care of health preservation; labor protection; social protection; help in acute life situations; catering; conducting cultural and sports programs; explanatory and consulting work (health care, pension issues, etc.). The structure of the integral part of the Trade Union Organization of the PUA - Trade Union of Students is considered and its main functional responsibilities are indicated: creation of a pro-staff in each academic group and organization of its work; conducting projects and programs to maintain a healthy lifestyle; patronage of senior courses over juniors and schoolchildren of the Specialized School of Economics and Law; assistance to students in solving educational and housing problems; organization of cultural and sports creative projects; holding a competition for the "Best Room" in the hostel; assistance in the organization of rest and improvement of students during the winter and summer vacations. The experience of the trade union committee in using the capabilities of all internal stakeholders of KhUH "PUA" to achieve a synergistic effect that facilitates the process of human adaptation to the conditions of constant change is presented.